2018
DOI: 10.1007/s00540-018-2512-x
|View full text |Cite
|
Sign up to set email alerts
|

Nalbuphine as an adjuvant to 0.25% levobupivacaine in ultrasound-guided supraclavicular block provided prolonged sensory block and similar motor block durations (RCT)

Abstract: Adding 20 mg nalbuphine to 25 ml of 0.25% levobupivacaine in supraclavicular block provided prolonged duration of sensory block with similar duration of motor block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Both nalbuphine and ketorolac infiltration prolonged the duration of analgesia and reduced the additional rescue analgesia rates and the postoperative consumption of morphine. As reported for other peripheral nerve blocks, our results show that nalbuphine and ketorolac infiltration have a postoperative opioid-sparing effect [10,16]. In addition, postoperative NRS pain scores within 12 h were lower in both the nalbuphine and the ketorolac infiltration groups compared with the ropivacaine alone group.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Both nalbuphine and ketorolac infiltration prolonged the duration of analgesia and reduced the additional rescue analgesia rates and the postoperative consumption of morphine. As reported for other peripheral nerve blocks, our results show that nalbuphine and ketorolac infiltration have a postoperative opioid-sparing effect [10,16]. In addition, postoperative NRS pain scores within 12 h were lower in both the nalbuphine and the ketorolac infiltration groups compared with the ropivacaine alone group.…”
Section: Discussionsupporting
confidence: 85%
“…Nalbuphine, a mixed agonist-antagonist opioid, was found to prolong the duration of analgesia in supraclavicular brachial block, subarachnoid block and epidural block as an adjuvant to local anesthetics. To the best of our knowledge, this aspect of nalbuphine infiltration has not been previously investigated [9][10][11] [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no differences in the incidences of nausea and vomiting among groups, but three patients in the R + HN group experienced nausea after surgery and two of them experienced vomiting. Prior studies have shown that nalbuphine added to ropivacaine or levobupivacaine prolonged the duration of sensory block and motor block in upper limb surgery [ 15 , 31 ]. Rao et al.…”
Section: Discussionmentioning
confidence: 99%
“…All the data were statistically analyzed by Statistical Package for the Social Sciences (SPSS) 19.0 software, the counting data were analyzed by X 2 test, the mean±standard deviation (x ̅ ±s) as used to represent the measurement data, the T test was used to compare the two groups of measurement data, and the analysis of variance was used to compare the multi group measurement data. commonly used drugs for preemptive analgesia [1] . Hydromorphinone hydrochloride is a semisynthetic opioid, a derivative of morphine, which plays an analgesic effect by activating opioid receptors in the central nervous system.…”
mentioning
confidence: 99%